Effect of Vacuum Packaging on Fish Products - Titi Rachmawati; Eka Andriani (Bulletin of Culinary Art and Hospitality, 2023)
Fish is one of the foodstuffs containing nutrients, especially protein, needed for the human body. In addition to protein, the nutrients contained in fish also vary. As a food source rich in nutritional content that can be easily found and obtained in Indonesia, many people have started making products or processed food from freshwater fish. Therefore, the quality of fish products, both in the form of direct products and processed products, must be maintained. Meanwhile, packaging factors can affect the growth of microorganisms such as fungi and bacteria. One of the packaging types is vacuum packaging. Vacuum packaging is one of the packaging methods with no air or oxygen within the packaging that is popular among the public. Therefore, the purpose of this study is to determine the effect of vacuum packaging, especially on fish products. Using descriptive analysis, this research adopted the qualitative research method. In addition to qualitative methods and descriptive analysis, this research also used a literature study method. Our results showed that the benefits of vacuum packaging for fish products are: 1) more durable and long-lasting products, 2) fresher products, and 3) more hygienic products because they are not airtight.